Artificial intelligence vs. human coaches: examining the development of working alliance in a single session - Amber S. Barger (Frontiers in Psychology)
The collaborative relationship, or working alliance, between a client and their coach is a well-recognized factor that contributes to the effectiveness of coaching. The rise of artificial intelligence (AI) challenges us to explore whether human-to-human relationships can extend to AI, potentially reshaping the future of coaching. Our presumption that the skills of professional human coaches surpass AI in forging effective relationships stands untested — but can we really claim this advantage? The purpose of this study was to examine client perceptions of being coached by a simulated AI coach, who was embodied as a conversational vocal live-motion avatar, compared to client perceptions of partnering with a human coach. The mixed methods randomized controlled trial explored if and how client ratings of working alliance and the coaching process aligned between the two coach types in an alternative treatments design. Both treatment groups identified a personal goal to pursue and had one 60-min session guided by the CLEAR (contract, listen, explore, action, review) coaching model. Quantitative data were captured through surveys and qualitative input was captured through open-ended survey questions and debrief interviews. To sidestep the rapid obsolescence of technology, the study was engineered using the Wizard of Oz approach to facilitate an advanced AI coaching experience, with participants unknowingly interacting with expert human coaches. The aim was to glean insights into client reactions to a future, fully autonomous AI with the capabilities of a human coach. The results showed that participants built similar moderately high levels of working alliance with both coach types, with no significant difference between treatments. Qualitative themes indicated the client’s connection with their coach existed within the context of the study wherein the coach was a guide who used a variety of techniques to support the client to plan towards their goal. Overall, participants believed they were engaging with their assigned coach type, while the five professional coaches, acting as confederates, were blinded to their roles. Clients are willing to and appreciate building coaching partnerships with AI, which has both research and practical implications.